Enhancing Employability Skills of Biology Graduates through an Interdisciplinary Project-Based Service Learning Experience with Engineering and Translation Undergraduate Students - José Luis González-Cespón; José Antonio Alonso-Rodríguez; Susana Rodríguez-Barcia; Pedro Pablo Gallego; Margarita R. Pino-Juste (MDPI AG, 2024)
We describe an interdisciplinary experience based on the application of the Project-Based Service Learning (PBSL) methodology for six learning outcomes directly related to employability skills. The objective was to assess students' learning outcomes, the level of satisfaction of students and lecturers with the PBSL, and the advantages and disadvantages of the implementation of this learning methodology. Interdisciplinary teamwork of undergraduate science, engineering, and humanities students was required to design real-world projects to develop their transferable skills, through the process of learning by doing. Students perceived that PBSL favored employability skills such as knowledge acquisition, self-directed learning, problem-solving, critical thinking, communication, and teamwork skills. Students and lecturers showed high satisfaction with PBSL and outlined its advantages as an active and experiential learning methodology. In conclusion, the implementation of the collaborative and interdisciplinary PBSL methodology is decidedly recommended to enhance Biology, Engineering, and Translation graduates' learning satisfaction and their future employability.